Exploration of Consumer Purchase Intentions for Blue Light Blocking Glasses in Indonesia - Eylda Syarah Dewi; Muhammad Akhdan Rahmani; Peri Akbar Manaf (Green Publisher Indonesia, 2024)
In the rapidly evolving information age, technological developments and social media significantly influence consumer purchasing decisions, especially in urban environments. This study explores the factors that influence the purchase intention of blue light glasses among urban consumers who use digital devices, using the Theory of Reasoned Action (TRA) framework. The factors analyzed include social media marketing, subjective norms, attitudes, hedonism, health values, social values, and knowledge. The survey was conducted among 306 respondents and analyzed by Structural Equation Modeling (SEM) using Partial Least Squares (PLS). The results show that marketing through social media, attitude, hedonism, health value, and knowledge have a positive effect on purchase intention, while social value shows a negative effect. This research provides insights for academics and practitioners in understanding consumer behavior and developing effective marketing strategies for anti-blue light glasses in Indonesia.